White Matter Injury in Preterm Infants: Pathogenesis and Potential Therapy From the Aspect of the Gut–Brain Axis - He, Yu; Zhang, Yuni; Li, Fang; Shi, Yuan (Frontiers in Neuroscience, 2022)
With a worldwide population of preterm birth, preterm brain injury is a predominant contributor to mortality and morbidity in NICU. Moreover, preterm infants who survived from brain injury are susceptible to impaired neurodevelopment in later life, which lead to subsequent economic burden. A broad spectrum of preterm brain injury ranges from white matter to grey matter, even cerebellar injury. White matter injury (WMI) is a unique and common form of brain injury in premature infants. Researches over the past decades indicate that the gut-brain axis plays a key role in WMI, involving major processes in neurodevelopment such as neurogenesis, the formation of the blood-brain-barrier, microglia maturation, and myelination. Herein, we discuss the crosstalk of preterm WMI and the gut microbiome, and elucidate the potential mechanisms by which the gut bacteria and the immature brain communicate with each other. The communication between gut microbiota and brain is ongoing via several pathways involving microbial metabolites, inflammatory and immune response characterized by microglial activation, and hypothalamic pituitary axis (HPA), which ultimately impact the differentiation of pre-myelinating oligodendrocytes and lead to WMI. Moreover, we focus on microbial-based intervention and treatment (such as probiotics and prebiotics) for preterm WMI.